Microglial Inflammation and Cognitive Dysfunction in Comorbid Rat Models of Striatal Ischemic Stroke and Alzheimer's Disease: Effects of Antioxidant Catalase-SKL on Behavioral and Cellular Pathology. (1st April 2022) - MacKenzie, Jennifer L.; Ivanova, Nadezda; Nell, Hayley J.; Giordano, Courtney R.; Terlecky, Stanley R.; Agca, Cansu; Agca, Yuksel; Walton, Paul A.; Whitehead, Shawn N.; Cechetto, David F.
Highlights: Brain ischemia in amyloid-β25–35 injected rat increases basal forebrain microgliosis. Increased striatal microglia inflammation in transgenic rat with ischemic stroke. Memory dysfunction in both co-morbid stroke and Alzheimer's disease rats. Antioxidant CAT-SKL decreased memory deficit and basal forebrain microgliosis. Abstract: Ischemic stroke often co-occurs with Alzheimer's disease (AD) leading to a worsened clinical outcome. Neuroinflammation is a critical process implicated in AD and ischemic pathology, associated with cognitive decline. We sought to investigate the combined effects of ischemic stroke induced by endothelin-1 injection in two AD rat models, using motor function, memory and microglial inflammation in the basal forebrain and striatum as readouts. In addition, we sought to determine the effectiveness of the antioxidant biologic CAT-SKL in one of the models. The early AD model employed the bilateral intracerebroventricular injections of the toxic β-amyloid peptide Aβ25–35, the prodromal AD model used the transgenic Fischer 344 rat overexpressing a pathological mutant human amyloid precursor protein. Motor function was assessed using a cylinder, modified sticky tape and beam-walk tasks; learning and memory were tested in the Morris water maze. Microglial activation was examined using immunohistochemistry. Aβ25–35 toxicity and stroke combination greatly increased microglial inflammation in the basal forebrain. Prodromal AD-pathology coupled with ischemia in the transgenic rat resulted in a greater microgliosis in the striatum. Combined transgenic rats showed balance alterations, comorbid Aβ25–35 rats showed a transient sensorimotor deficit, and both demonstrated spatial reference memory deficit. CAT-SKL treatment ameliorated memory impairment and basal forebrain microgliosis in Aβ25–35 rats with stroke. Our results suggest that neuroinflammation could be one of the early processes underlying the interaction of AD with stroke and contributing to the cognitive impairment, and that therapies such as antioxidant CAT-SKL could be a potential therapeutic strategy.